2009
DOI: 10.1007/s15010-008-8203-z
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Global Research Excellence in Severe Sepsis (PROGRESS): Lessons from an International Sepsis Registry

Abstract: The PROGRESS international sepsis registry demonstrates that a large web-based sepsis registry is feasible. Wide variations in outcomes and use of sepsis therapies were observed between countries. These results also suggest that additional opportunities exist across countries to improve severe sepsis outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
1
23

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(132 citation statements)
references
References 45 publications
5
103
1
23
Order By: Relevance
“…A recent meta‐analysis of RCTs reported that the survival benefit of anticoagulant therapy was observed only in sepsis patients with DIC, but not in those without DIC 10. Furthermore, although many epidemiological studies for sepsis have been carried out,11, 12, 13, 14, 15 epidemiological data regarding sepsis in Japan is limited 16, 17…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta‐analysis of RCTs reported that the survival benefit of anticoagulant therapy was observed only in sepsis patients with DIC, but not in those without DIC 10. Furthermore, although many epidemiological studies for sepsis have been carried out,11, 12, 13, 14, 15 epidemiological data regarding sepsis in Japan is limited 16, 17…”
Section: Introductionmentioning
confidence: 99%
“…(2,(18)(19)(20)(21)(22)(23) In Brazil it is higher than in other countries, 56% of mortality versus 30% in the developed countries and 45% in other developing countries. (2,24) Possibly these high rates are due to delay in starting therapy which greatly contributes to spreading of the inflammatory response and development of multiple organ dysfunction (MOD). Patients under treatment, even when appropriate, after multiple organ dysfunction have a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Eldicus developed an ICU triage score in 11 European countries and found respiratory rate to be missing in 44% of 6796 patients triaged for ICU and 50% of 794 septic patients [13]. Data are mostly from the USA, where two qSOFA components predict mortality [3] but where mortality rates are lower than in LMICs [14]. Perhaps only one rather than two qSOFA components should be necessary, especially in LMICs with a higher mortality.…”
Section: The Badmentioning
confidence: 99%